Contemporary Educational Trends in Islamic Education: An Analytical Review of Pedagogical Challenges and Strategic Opportunities - Aboubacar Barry; Mohamed Iyas Valarthodi; Mohamad Ali; Rizqianto Hermawan; Jafar Ihza Yuska Azzacky (LECTURES: Journal of Islamic and Education Studies, 2025)
Islamic education is undergoing significant transformation due to the increasing adoption of contemporary educational trends, including digital learning, competency-based education, and interdisciplinary curriculum reform. However, balancing these modern educational advancements with the preservation of Islamic pedagogical values remains a challenge. This study employs a semi-systematic literature review to analyze the impact of contemporary trends on Islamic education, highlighting key challenges and strategic opportunities. The research synthesizes findings from peer-reviewed journal articles and academic databases, focusing on three core areas: (1) technology integration in Islamic education, (2) curriculum reform and pedagogical innovations, and (3) institutional policies and educator development. The findings reveal that while digital learning enhances accessibility and engagement, infrastructure limitations, digital literacy gaps, and concerns over content authenticity persist. Additionally, resistance to interdisciplinary curriculum reform poses challenges to achieving a balanced educational approach. Institutional policies and educator training programs play a crucial role in addressing these challenges by promoting competency-based learning, professional development for teachers, and digital infrastructure expansion. The novelty of this study lies in its comparative analysis of policy interventions and technological advancements in Islamic education across different regional contexts. This research contributes to the discourse on Islamic education modernization by offering a framework for sustainable reforms that respect Islamic values. Future research should explore longitudinal assessments of digital learning outcomes, empirical studies on policy implementation, and the role of artificial intelligence in Islamic pedagogy.